2014
DOI: 10.5489/cuaj.2316
|View full text |Cite
|
Sign up to set email alerts
|

Elective gangrene of the corpus spongiosum of idiopathic origin: A case report

Abstract: Cite as: Can Urol Assoc J 2014;8(11-12):e934-7. http://dx.doi.org/10.5489/cuaj.2316 Published online December 15, 2014. AbstractPenile gangrene is rare and associated with significant morbidity and mortality. It can be dry or wet. Treatment for dry gangrene is based on surgery, watchful waiting allowing spontaneous amputation of necrotic tissue or revascularization. It often depends on the general condition of the patient. We report a case of a 54-year-old patient with no significant medical history who presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The authors reported a poor prognosis with calciphylaxis-related necrosis. Kharbach and colleagues reported a 54-year-old patient with idiopathic necrosis of the glans penis managed with partial penectomy [ 9 ]. Agustino and Irdam reported a 30-year-old male with ischemic related to aortic dissection who presented with acute limb ischemia, necrosis of the penis, and scrotum gangrene managed with debridement of the penis and scrotum and urinary diversion with percutaneous cystostomy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a poor prognosis with calciphylaxis-related necrosis. Kharbach and colleagues reported a 54-year-old patient with idiopathic necrosis of the glans penis managed with partial penectomy [ 9 ]. Agustino and Irdam reported a 30-year-old male with ischemic related to aortic dissection who presented with acute limb ischemia, necrosis of the penis, and scrotum gangrene managed with debridement of the penis and scrotum and urinary diversion with percutaneous cystostomy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic penile gangrene is a rare and understudied urologic condition associated with significant morbidity. The disease has been associated with diabetes mellitus, renal insufficiency, paraphimosis, priapism, tourniquet syndrome, venous outlet obstruction, and IV drug use [1] , [2] , [3] . Our knowledge of the condition remains limited, and it still occurs in patients without any clear cause.…”
Section: Introductionmentioning
confidence: 99%
“…The internal pudendal arteries further branch into the bulbourethral arteries, which supply the bulb and penile urethra, the dorsal penile arteries, which supply the glans, and the cavernosal arteries, which play an integral role in the process of tumescence and erection. This complex arterial network is important in maintaining the physiological function of the penis [2] .…”
Section: Introductionmentioning
confidence: 99%
“…On investigation, X-ray abdomen and pelvis showed impacted urethral calculus measuring 16 × 12 mm. Hemogram showed hemoglobin 11 gm/dL, platelet count 77,000/mm 3 , and total leukocyte count 8800/mm 3 . His other laboratory tests, such as renal function test, liver function test, and random blood sugar were within normal limits.…”
Section: Case Reportmentioning
confidence: 99%
“…Fournier's gangrene of penis with involvement of corpus spongiosum leading to loss of penile urethra is an uncommon finding. 1,5,6 Resident, 2 Associate Professor, 3 Professor and Head 4 Lecturer 1-6 Department of Urology, MGM Medical College, Navi Mumbai Maharashtra, India Corresponding Author: Saket Sathe, Resident, Department of Urology, MGM Medical College, Navi Mumbai, Maharashtra India, Phone: +919665500090, e-mail: saketsathe123@yahoo. co.in…”
Section: Introductionmentioning
confidence: 99%